Novel Mutations in TSEN54 in Pontocerebellar Hypoplasia Type 2. (April 2014) - Battini, Roberta; D'Arrigo, Stefano; Cassandrini, Denise; Guzzetta, Andrea; Fiorillo, Chiara; Pantaleoni, Chiara; Romano, Alessandro; Alfei, Enrico; Cioni, Giovanni; Santorelli, Filippo M.
Pontocerebellar hypoplasias represent a group of neurodegenerative autosomal recessive disorders characterized by hypoplasia/atrophy of the cerebellum, hypoplastic ventral pons, and microcephaly and associated with various clinical features. Pontocerebellar hypolasia type 2 is the most common form, and different mutations in genes encoding subunits of the transfer ribonucleic acid (RNA)–splicing endonuclease ( TSEN ) complex were identified in patients. The authors report clinical, imaging, and molecular studies in 2 unrelated patients with different clinical pictures of the pontocerebellar hypoplasia type 2 spectrum and novel mutations in TSEN54, aiming to further define the clinical spectrum of the disease and possible indicators of more favorable progression. They identified a novel missense mutation c.355T>G/p.Y119D in compound heterozygosity with the "common" c.919G>T/p.A307S (patient 1) and a novel homozygous c.7ins6(CCGGAG)/p.E2-P3insPE variant (patient 2). An expanded array of mutations might contribute in defining possible differences in severity and phenotype-genotype correlations.